2004
DOI: 10.1128/jcm.42.8.3419-3427.2004
|View full text |Cite
|
Sign up to set email alerts
|

Sex Pheromone Response, Clumping, and Slime Production in Enterococcal Strains Isolated from Occluded Biliary Stents

Abstract: Bile-resistant bacteria, particularly gram-positive Enterococcus faecalis and Enterococcus faecium, play an important role in biliary stent occlusion, because their sessile mode of growth protects them against host defenses and antimicrobial agents. Twelve E. faecalis and seven E. faecium strains isolated from occluded biliary stents have been investigated for slime production, presence of aggregation substance genes, and ability to adhere to Caco-2 cells. Ten isolates were strong producers of slime, and seven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 30 publications
3
20
1
Order By: Relevance
“…The intra-and interspecies transferability of tcrB gene in our study is in agreement with our earlier studies with pig isolates (10,11). Interestingly, the conjugation frequency was higher in the interspecies assay, possibly because of the production of pheromones (peptide signal) by the recipient E. faecalis isolate strains, which are specific for a particular plasmid or a group of related plasmids (37,38). In this pheromone-inducible plasmid transfer, the recipient bacterium excretes the peptide pheromone molecule into the medium, where it can diffuse to a donor cell, thus facilitating transfer of antibiotic resistance determinants.…”
Section: Discussionsupporting
confidence: 81%
“…The intra-and interspecies transferability of tcrB gene in our study is in agreement with our earlier studies with pig isolates (10,11). Interestingly, the conjugation frequency was higher in the interspecies assay, possibly because of the production of pheromones (peptide signal) by the recipient E. faecalis isolate strains, which are specific for a particular plasmid or a group of related plasmids (37,38). In this pheromone-inducible plasmid transfer, the recipient bacterium excretes the peptide pheromone molecule into the medium, where it can diffuse to a donor cell, thus facilitating transfer of antibiotic resistance determinants.…”
Section: Discussionsupporting
confidence: 81%
“…For ␤-hemolysis detection, strains were grown on horse blood agar plates for 1 to 2 days at 37°C. Biofilm formation was tested using the slime production assay described previously (17).…”
Section: Methodsmentioning
confidence: 99%
“…Esp is a surface protein involved in the ability to colonize and in immune evasion in E. faecalis and E. faecium (21,24). Enterococci are also known to produce slime (17,18) and to form biofilms, which have been regarded as virulence features of clinical isolates (16,18). North 1997 VI1, VI46 2002 MI24, MI25, MI26, MI28, MI29, MI30, MI31, MI32, MI33, MI34, MI54, MI55, MI56, MI57, MI58, MI59, MI60 Center 1997 AN8 2002 AN7, AN9, AN12, AN13, AN14, AN15, AN16, AN17, AN19, AN20, AN23, AN47, AN48, AN49, AN50, AN51, Several reviews have addressed the genetic basis, reservoirs, and spread of glycopeptide resistance in enterococci (7,9,51) and enterococcal virulence (24,27,47).…”
mentioning
confidence: 99%
“…This study indicates that the production of slime exhibited by most enterococcal isolates plays an important role in the colonization and subsequent occlusion of biliary stents, suggesting that aggregation substance is implicated in the occlusion process and that enterococci carrying aggregation substance genes have a selective advantage in endoprosthesis colonization. [54][55][56] The accumulation of biliary sludge is thought to be a multifactorial process in which, other than microbial growth, slime production and biofilm formation, a significant role is played by some bacterial enzymes (table 2). Chemical analyses have shown that, in addition to the nonbacterial constituents listed in table 2, calcium bilirubinate and calcium palmitate are commonly present in biliary sludge.…”
Section: Causative Factors and Dynamics Of The Clogging Process In Plmentioning
confidence: 99%